FDI from BRICs to LICs : Emerging Growth Driver? - Mlachila, Montfort (IMF Working Papers; Working Paper, 2011)
Despite the rapid increase in FDI flows to LICs, there have been relatively few studies that have specifically examined these flows. This paper attempts to partially fill the void by throwing light on one particularly dynamic aspect of global FDI-flows from Brazil, Russia, India and China (BRICs). The paper finds that official data sources undoubtedly underestimate the volume and scope of FDI flows as many small and medium-sized enterprises (SMEs) do not always register their investment. As a result, while it is difficult to estimate accurately the growth impact of BRIC FDI, there is case study evidence that it is increasingly significant. Second, while initial investment, mostly by state-owned companies, has often been destined for natural resource industries, over time, investment has been spreading to agriculture, manufacturing, and service industries (e.g., telecommunications). Third, FDI from BRICs flows into many non resource-rich countries in LICs and plays a significant role in growth in those countries.